A Novel Paclitaxel Coated Drug Eluting 316L Stents - G. RAJENDER,; N.G.B. NARAYAN,; G. BENARJEE,; E. NARAYANA, (International Journal of Pharma and Bio Sciences, 2010)
LCMS/MS method was used (ESI +Source) to determine the concentration of Paclitaxel coated drug eluting stents (316 LVM). LCMS/MS has proved to be a powerful research tool due to its sensitivity, high selectivity, and high throughput efficiency to determine drug concentration of the sample. The elution kinetics was carried out on flow through dissolution apparatus-USP-4 (Sotax) .The samples were collected according to study design.The extraction process of the elution samples were on Liquid –Liquid extraction procedure. Chloroform was used as extraction solvent. The evaporated samples were reconstituted with mobile phase (80:20+0.1% acetic acid). LCMS/MS, triple quadropole Separation was achieved using phenomenax C-18 column (250x4.60mm 5microns). The flow rate was set to 0.8ml/min. UV detection of paclitaxel was at 228nm.Total run time was 6.0 for each run. Drug release was observed in first hour of implantation of the stent. Percentage of drug release was increased 24 hours, later it was stable. The maximum of Paclitaxel was released in first two days. The cumulative percentage of drug release was 50% in 12 days .This was based on the polymers (PLA/PLGA) and drug interaction. Release was based on the composition of the drug and polymer composition. The studies of the paclitaxol coated drug eluted stents were preventing early thrombosis.